Integrated Wireless Pointing Device, Terminal Equipment with the Same, and Pointing Method Using Wireless Pointing Device (2005)
A wireless pointing device, a terminal equipment with the same, and a pointing method using the wireless pointing device are disclosed. A disclosed wireless pointing device includes a lighting means, an image acquisition area, an image formation means, a light receiving means, a movement detection means, and a wireless communication means. The subject is the surface of a finger, a lattice pattern or a perceivable pattern. One example wireless pointing device is combined with a fingerprint sensor to collect a user's fingerprint during operation of the pointing device and compare the fingerprint with an existing registered fingerprint without a separate fingerprint authentication procedure. A disclosed wireless pointing method includes displaying and activating menu items requiring a settlement service and personal information if a user's fingerprint is identical with a registered fingerprint, and deactivating menu items requiring a settlement service and personal information if a user's fingerprint is not identical with a registered fingerprint.